Talent Management in International Practice Through the Example of Europe and China - Héder, Mária (International Journal of Engineering and Management Sciences, 2018)
The reason behind is that they have their own principles, strategic goals and industrial environment that they have to manage on daily bases. The current labour and talent shortage across Europe forces local companies to supply their demand of manpower from foreign countries – encouraged by the ’four freedoms’ of the EU. In consequence of the globalisation, we have to keep in mind that running a talent management system has its challenges. For instance, employees with different cultural background might have unconventional needs. Due to the cultural, demographical and economical differencies, we must know the structure of our labour force to use the most beneficial tools to induct, motivate or retain our human resource. The aim of this research is to analyze Europe’s and China’s talent management systems to reveal similarities and differencies between them and pick the most notable ones. From the point of comparison, analysing China would be important for European countries to discover further possibilities, as nowadays China has one of the most dynamically developing economy with enormous population behind. The primary result of the research is that deficiency of talent is irrespective of the size of the population and it causes difficulty in both European and Chinese fields, therefore it proves to be a real and general challenge needing attention at organizational level. Furthermore, identifying regional patterns considering peculiarities, the framework of talent management systems can be defined and be found summarised in the article.